Pulsed electric field (PEF): Avant-garde extraction escalation technology in food industry. (April 2022) - Naliyadhara, Nikunj; Kumar, Aviral; Girisa, Sosmitha; Daimary, Uzini Devi; Hegde, Mangala; Kunnumakkara, Ajaikumar B.
Abstract: Background: Pulsed Electric Field (PEF) technology is a non-thermal approach mainly used to preserve food with higher electrical conductivity, such as liquid or semi-liquid foods. PEF uses an electric field to create irreversible poration in the cell membrane, increasing membrane permeability. The application of PEF to increase the extraction rate in the food and nutraceutical industry is still in its infancy. Scope and approach: This study describes the mechanism of PEF treatment and its effect on food's quantitative and qualitative attributes. This review emphasizes the significance of PEF treatment on the extraction of various compounds from the food matrix like juices, edible oils, bioactive compounds, and carbohydrates. Key findings and conclusion: A plethora of literature evinced that the application of PEF treatment to extract fruit juices, edible oils, various bioactive compounds, and carbohydrate compounds on a laboratory scale and pilot-level scale have significantly affected the extraction yield. Moreover, PEF treatment allows preserving the end product's quality in terms of sensory and nutritional aspects. Various studies have shown PEF as a productive tool to utilize the waste of agro-processing industries for recovering multiple bioactive compounds that could be economically beneficial. PEF becomes an optimal choice for pretreatment before extraction due to its desirable traits such as minimal operational period and efficient power consumption. Though extensive research has been carried out at a laboratory scale, there is a need to explore the PEF on the industrial scale further and optimize various PEF parameters to obtain high productivity. Highlights: PEF is a non-thermal approach which can be utilized as pretreatment prior to extraction operation in Food Industry. Pulsed electric field uses electric pulses to destroy microbial and plant cells. PEF treatment leads to high efficiency, shorter extraction time and less energy usage. PEF can be used to extract bioactive ingredients from fruits, vegetables, agricultural waste and microbes. PEF was compared to other advanced technologies such as MWAE, UAE, and HVED.